Factors affecting human resource agility: A literature review and future research directions - Athamneh M.H.A.; Jais J. (Cogent OA, 2024)
This article gives a contextual understanding of human resource agility by highlighting organizational factors that influence it. The existing literature lacks assessments of the level of knowledge on this subject. The objective of this research was to address this gap by examining scholarly advancements in the area of human resources agility. To accomplish this, researchers reviewed all of the articles that would have been available in various electronic databases up to 2022. Conceptually, the data enabled us to determine that the agility of human resources comprised three connected dimensions: proactivity, resilience, and adaptation. One can acquire these characteristics through I) effective communication, II) delegation of authority, III) decision-making, and IV) work teams. This study also allowed us to suggest a plan for future research on the agility of human resources and other related topics. This article highlights the significance of human resource agility and its potential impact on business competitiveness, particularly in developing nations. It also brings attention to a topic that has limited discussion in academic literature. 2023 The Author(s). This open access article is distributed under a Creative Commons Attribution (CC-BY) 4.0 license.